Commentary: Impacts of the Larsen-C Ice Shelf calving event - Hogg, Anna; Gudmundsson, Hilmar (Nature Climate Change, 2017)
A giant iceberg has calved off the Larsen-C Ice Shelf, the largest remaining ice shelf on the Antarctic Peninsula, reducing its total area by ~10%. Whilst calving events are a natural phenomenon and thus not necessarily indicative of changing environmental conditions, such events can impact ice-shelf stability.